Perceptions of university students on gender equality. A review from its sociocultural context - Guerrero-Azpeitia, Luis Arturo (2023)
The objective was to explore the perceptions that university students express regarding gender equality based on their sociocultural context. Some elements of Bourdieu's sociological perspective were recovered, in order to approach said object of study as a production of subjectivity from the objective conditions of the students. Methodologically, a questionnaire was designed with the intention of recovering elements of the students' sociocultural context and at the same time exploring their perceptions of the gender perspective; Data treatment was performed through multiple correspondence analysis. The main results highlight the relationship between the social conditions of the students, such as the schooling of their parents and their economic activity, and their perceptions of gender equity. Finally, it can be concluded the importance of family sociocultural conditions in shaping the perceptions and opinions of university students.